Conservation agriculture: towards managing the water-energy-food nexus in India - Sikka, Alok (2021)
Depleting groundwater resources and increasing energy demand with the huge dependence of India’s agriculture on groundwater and energy, and especially in water deficit rice-based production systems, are posing a serious threat to sustained food, water, and energy security. Sustainability concerns of water, energy, and input-intensive rice-based crop production systems have increased the realization for developing and scaling up alternative agro-techniques that can significantly reduce the water and energy requirements in crop production without compromising on crop yield. The interconnectedness between water, energy, and food makes the concept of water, energy, and food (WEF) nexus more relevant to explore integrated solutions to efficient use of limited and/or declining water and energy resources. Conservation agriculture (CA) is gaining currency as an alternate system for rice/cereal-based production systems to conserve water and energy, improve soil health, reduce cost of cultivation, and preserve ecology. This paper explores the concept of WEF nexus and how CA addresses the challenge of harmonizing the synergy among water, energy, and food though WEF ‘nexus gains’ especially in the context of groundwater irrigated rice/cereal based cropping systems.